2001
DOI: 10.1182/blood.v98.12.3324
|View full text |Cite
|
Sign up to set email alerts
|

Response to hypoxia involves transforming growth factor-β2 and Smad proteins in human endothelial cells

Abstract: Oxygen deprivation (hypoxia) is a consistent component of ischemia that induces an inflammatory and prothrombotic response in the endothelium. In this report, it is demonstrated that exposure of endothelial cells to hypoxia (1% O 2 ) increases messenger RNA and protein levels of transforming growth factor-␤2 (TGF-␤2), a cytokine with potent regulatory effects on vascular inflammatory responses. Messenger RNA levels of the TGF-␤2 type II membrane receptor, which is a serine threonine kinase, also increased. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 84 publications
5
54
1
Order By: Relevance
“…Several studies have reported that modulation of oxygen tension was recognized as an important regulator of gene activation of TGF-b in rat brain and liver, and human fibroblast and hepatoma cells [19][20][21][22]. Recently, it was also reported that cell response to hypoxia involved signaling via Smad protein in hypoxia endogelial cells by producing TGF-b with autocrine regulation [23,24]. In this study, we measured the expression level of TGF-b1 and the phosphorylation level of its downstream protein Smad2 in order to reveal the relationship between hypoxia and intracellular TGF-b signal transduction during fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that modulation of oxygen tension was recognized as an important regulator of gene activation of TGF-b in rat brain and liver, and human fibroblast and hepatoma cells [19][20][21][22]. Recently, it was also reported that cell response to hypoxia involved signaling via Smad protein in hypoxia endogelial cells by producing TGF-b with autocrine regulation [23,24]. In this study, we measured the expression level of TGF-b1 and the phosphorylation level of its downstream protein Smad2 in order to reveal the relationship between hypoxia and intracellular TGF-b signal transduction during fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…9 Since the TGF-␤ family of proteins can regulate their own transcription and synthesis, 40 it is possible that hypoxiadriven up-regulation of TGF-␤2 gene expression is part of an autocrine pathway triggered by hypoxia-induced bioactivation of the TGF-␤ ligand. Since transcript and protein levels of TSP-1 have been shown to be increased in hypoxic endothelial cells in a time course parallel to hypoxic induction of the TGF-␤2 gene, 46 we tested whether hypoxia-induced bioactivation of TGF-␤ was TSP-1-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…37 Cells were maintained in Dulbecco modified Eagle medium (BioWhittaker, Walkersville, MD) containing 10% fetal calf serum, 2 mM L-glutamine, and antibiotics (penicillin G, 100 U/mL; streptomycin, 100 g/mL; and geneticin, 250 g/mL [Gibco BRL, Grand Island, NY]), and levels of bioactive TGF-␤ in HUVEC supernatants were determined as previously described. 9,36 Briefly, MLECs were detached with trypsin, washed, plated at 1.6 ϫ 10 5 cells per well in a 2-mL volume in 24-well tissue culture plates (Costar, Cambridge, MA), and allowed to attach for 18 hours at 37°C in 5% CO 2 . Medium in the wells was replaced by 2 mL of the following, placed in triplicate wells: control medium, control medium containing increasing concentrations of recombinant TGF-␤2 to generate a standard curve, and 1:10 dilution of conditioned HUVEC medium to measure bioactive TGF-␤.…”
Section: Reagentsmentioning
confidence: 99%
See 2 more Smart Citations